Synergism between IL-33 and MRGPRX2/FcεRI Is Primarily Due to the Complementation of Signaling Modules, and Only Modestly Supplemented by Prolonged Activation of Selected Kinases - Kristin Franke; Zhuoran Li; Gürkan Bal; Torsten Zuberbier; Magda Babina (Cells, 2023)
Skin mast cells (MCs) express high levels of MRGPRX2, FcεRI, and ST2, and vigorously respond to their ligands when triggered individually. IL-33/ST2 also potently synergizes with other receptors, but the molecular underpinnings are poorly understood. Human skin-derived MCs were stimulated via different receptors individually or jointly in the presence/absence of selective inhibitors. TNF was quantified by ELISA. Signaling cascades were studied by immunoblot. TNF was stimulated by FcεRI ≈ ST2 > MRGPRX2. Surprisingly, neither FcεRI nor MRGPRX2 stimulation elicited NF-κB activation (IκB degradation, p65 phosphorylation) in stark contrast to IL-33. Accordingly, TNF production did not depend on NF-κB in FcεRI- or MRGPRX2-stimulated MCs, but did well so downstream of ST2. Conversely, ERK1/2 and PI3K were the crucial modules upon FcεRI/MRGPRX2 stimulation, while p38 was key to the IL-33-elicited route. The different signaling prerequisites were mirrored by their activation patterns with potent pERK/pAKT after FcεRI/MRGPRX2, but preferential induction of pp38/NF-κB downstream of ST2. FcεRI/MRGPRX2 strongly synergized with IL-33, and some synergy was still observed upon inhibition of each module (ERK1/2, JNK, p38, PI3K, NF-κB). IL-33’s contribution to synergism was owed to p38 > JNK > NF-κB, while the partner receptor contributed through ERK > PI3K ≈ JNK. Concurrent IL-33 led to slightly prolonged pERK (downstream of MRGPRX2) or pAKT (activated by FcεRI), while the IL-33-elicited modules (pp38/NF-κB) remained unaffected by co-stimulation of FcεRI/MRGPRX2. Collectively, the strong synergistic activity of IL-33 primarily results from the complementation of highly distinct modules following co-activation of the partner receptor rather than by altered signal strength of the same modules.